Determinants of Pension Fund’s Required Return: A Scenario-based simulation of Civil Service Pension Fund - Muhammad Irfan; Wee-Yeap Lau (Australasian Accounting, Business and Finance Journal, 2023)
This study examines the required return to fund a defined pension benefit of the Civil Service Pension Fund, managed by KWAP. Based on the four variables, contribution rate, retirement age, life expectancy, and length of service, this study simulates 648 scenarios of required return corresponding to the years of service and post-retirement benefits. Our findings show: First, the minimum years of service for the pension eligibility shall be increased to 20 years. Second, the Government shall increase the contribution rate to at least 13% per worker to KWAP. Third, there are no significant changes in the required rate of return even though the Government extended the retirement age from 55 to 60. Hence, extending the retirement age will not reduce the pension cost. Fourth, this study shows that the contribution period is more crucial than the post-retirement period for the Government to sustain the pension fund. Lastly, there is a need for the Government to set a minimum funding ratio for the KWAP pension fund to ensure its long-term sustainability. As a policy suggestion, the current pension fund needs refinement to ensure long-term sustainability.
Keywords: Public Pension; Malaysia; Investment Performance; Internal Rate of Return; Scenario Analysis; Simulation